2020
DOI: 10.1515/ntrev-2020-0087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cinnamon essential oil on morphological, flammability and thermal properties of nanocellulose fibre–reinforced starch biopolymer composites

Abstract: The effect of different cinnamon essential oil (CEO) contents on flammability, thermal stability and morphological characteristics of nanocellulose fibre–reinforced starch biopolymer composites was studied. This sugar palm nanocellulose reinforced with sugar palm starch, containing 0–2% CEO, was prepared through solution casting technique. From scanning electron microscopy analysis, the cross-sections of the CEO-containing films showed appearance of micro-porous spots as micro-porous holes because of the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 90 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…The intensity changes at the 1756 cm −1 peak showed the esterification among the -OH groups of SP fiber and -COOH terminal groups of PLA. A small peak in all nine samples at 2995 cm −1 was ascribed with the frequency of the O-H group [72,73]. This intensity was also decreased after treatment of SPF.…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 77%
“…The intensity changes at the 1756 cm −1 peak showed the esterification among the -OH groups of SP fiber and -COOH terminal groups of PLA. A small peak in all nine samples at 2995 cm −1 was ascribed with the frequency of the O-H group [72,73]. This intensity was also decreased after treatment of SPF.…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 77%
“…To identify the changes that occurred in the chemical structures of the films by adding different plasticizers at different concentrations, FTIR analysis was conducted to investigate the intermolecular rearrangement of polysaccharide chain orientation, as shown in Figure 5 [75]. The control film showed peaks at 890.23, 1019.91, 1653.21, 2942.45, and 3358.15 cm −1 .…”
Section: Spectroscopy Analysis Of the Film Using Ftirmentioning
confidence: 99%
“…The reason for this can be explained as the deterioration in the structure of the film and the observation of holes as a result of the evaporation of the films during drying, since CZE contains volatile components. A similar study reported that with the addition of different proportions of CZE to the starch–nanocellulose fibre composite, coarse and microstructured holes were formed in the films (Syafiq et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%